Redistributing Income under Proportional Representation - David Austen-Smith (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
Most of the theoretical work on purely redistributive taxation has presumed a two-party model in which the parties choose (affine) tax policies to attract a majority of voters. However, while majoritarian decision rules are the norm in legislatures, relatively few democratic electoral systems use simple majority rule at the electoral stage, adopting instead some form of multiparty proportional representation. Moreover, aggregate data suggest that average income tax-rates are higher and distributions of post-tax income flatter, in countries with proportional representation than in those with plurality rule. While there are other differences between these countries, this paper explores how variations in the political system per se influence equilibrium redistributive tax-rates and income distributions. In particular, a three-party proportional representation model is developed in which taxes are determined through legislative bargaining among successful electoral parties, and the fundamental economic decision for individuals is occupational choice. Political-economic equilibria for this model and for a two-party, winner-take-all, majoritarian system are derived and compared.
Keywords: 330